Edukasi Blefaritis dan Pemeriksaan Mata dengan Media PowerPoint di Dusun II Barat Tanjung Gusta: Blepharitis Education and Eye Examination with PowerPoint Media in Dusun II Barat Tanjung Gusta - Simorangkir, Saharnauli Janna Verawaty; Marpaung, Dina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Blepharitis is one of the complaints of eye disease that most often makes patients go to the clinic. Signs and symptoms of blepharitis are varied and may be associated with various dermatological conditions, such as seborrheic dermatitis, rosacea, and allergies. Blepharitis can also be acute and chronic. Blepharitis sufferers often come with complaints that are chronic and recurring. Therefore, it is deemed necessary to provide education about this disease and how to prevent it most effectively. This community service aims to provide education about blepharitis, its signs and symptoms, and how to prevent it, and at the same time, provide free eye examinations to all counseling participants. This community service activity was conducted through counseling and a media presentation regarding blepharitis. At the beginning and end, a pretest and post-test were carried out to assess changes in the level of knowledge of all participants regarding counseling. The number of counseling participants who attended was 36 people, of which 12.5% were men, and 88.8% were women, with an age range between 20-70 years, and the most age range was in the 41-50 year range. The results of counseling activities regarding blepharitis obtained as many as 31 people (86.1%) participants experienced an increase in pretest and post-test results, and most of the participants, namely as many as five people (13.9%), showed consistent post-test results. The evaluation of this activity showed that most participants thought it went well (55.6%), and all participants agreed that this community service activity was very beneficial for them.